An Investigation of The Connection of Bloom’s Taxonomy to the Core Mathematics Curriculum for Senior High Schools in Ghana - Amoako Atta, Seth; Atta, Solomon Ohene Amoako; Belbase, Shashidhar; Assan, Francis Kwaku; Samuel, Amoako (Golden Ratio of Social Science and Education, 2024)
This paper attempts to preview the connection of Bloom's taxonomy to Ghana's Senior High School mathematics curriculum. Mathematics is a vital tool for economic growth and national development as a STEM subject. Bloom's taxonomy, which presents a hierarchical model, helps educators teach school mathematics to enable students to acquire basic Knowledge known as order thinking (LOT) skills and develop higher-order thinking (HOT) skills. The analysis of the mathematics syllabus concerning Bloom's taxonomy revealed that the syllabus concentrates more on the three fundamental skills in Bloom's hierarchy of teaching and assessment. Remember 18.1%, Understand 33.3%, and Apply 29.8%, totalling 81.2%, leaving only 18.8% for the top three HOT skills. The study recommends that Ghana adopt a curriculum model that focuses on teaching transversal skills that can churn out informed citizens rather than putting students under the shackles of tests.